2003
DOI: 10.1159/000071267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RS-601, a Novel Leukotriene D<sub>4</sub>/Thromboxane A<sub>2</sub> Dual Receptor Antagonist, on Asthmatic Responses in Guinea Pigs

Abstract: The effects of 4-[4-[5,5,6,6,6-pentafluoro-1-(4-fluorobenzene-sulfonamido)hexyl]phenyl]butyric acid (RS-601), a novel leukotriene D4 (LTD4)/thromboxane A2 (TxA2) dual receptor antagonist, on bronchial asthmatic responses in guinea pigs were examined. The effects were compared with those of pranlukast (LTD4 receptor antagonist) and S-1452 (TxA2 receptor antagonist). RS-601 inhibited the increase in airway resistance caused by LTD4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Indeed, these have been shown to be effective when used either alone or in combination for suppressing antigen-induced bronchoconstriction in guinea pigs (Yoshimi et al, 2001). Other drugs have been developed with dual leukotriene D4 and TXA 2 receptor antagonism with efficacy in experimental models of allergic inflammation (Yamada et al, 2003;Ishimura et al, 2006). However, the efficacy of TXA 2 synthase inhibitors and receptor antagonists does not spread to all inflammatory diseases where activated platelets are a component.…”
Section: Antagonists Of Pleiotropic Mediators Released By Plateletsmentioning
confidence: 99%
“…Indeed, these have been shown to be effective when used either alone or in combination for suppressing antigen-induced bronchoconstriction in guinea pigs (Yoshimi et al, 2001). Other drugs have been developed with dual leukotriene D4 and TXA 2 receptor antagonism with efficacy in experimental models of allergic inflammation (Yamada et al, 2003;Ishimura et al, 2006). However, the efficacy of TXA 2 synthase inhibitors and receptor antagonists does not spread to all inflammatory diseases where activated platelets are a component.…”
Section: Antagonists Of Pleiotropic Mediators Released By Plateletsmentioning
confidence: 99%
“…KP-496 significantly inhibited AHR in this model. Another study using the same model [22] demonstrated that pranlukast and S-1452 were ineffective against AHR and that RS-601 suppressed AHR, and this suggested that both cysLTs and TXA 2 play important roles in AHR in this model. Therefore, this result was also due to both the anti-cysLT and anti-TXA 2 effects of KP-496.…”
Section: Discussionmentioning
confidence: 78%
“…Many reports have suggested that chemical mediators derived from arachidonic acid, such as cysLTs, TXA 2 and platelet-activating factor, participate in the development of LAR [3,[28][29][30] . Another group reported that pranlukast and RS-601, another dual antagonist of cysLTs and TP, suppressed LAR but that S-1452, a TP antagonist, did not suppress LAR in this model [22] . It has also been reported that a higher dose of S-1452 suppressed LAR [25] .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results suggest that an antagonist for both TXA 2 and LTD 4 receptors would be more effective in the treatment of asthma, compared to the selective antagonists. Some TXA 2 and LTD 4 dual receptor antagonists, such as RS-601 16) and YM-158, [17][18][19][20][21][22] have been reported to have potent efficacy in various antiasthmatic models.…”
mentioning
confidence: 99%